Identity, interest, and politics: the rise of Kurdish associational activism and the contestation of the state in Turkey - Kılıç, Azer. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2013., 2013)
This dissertation investigates associational behaviour in a context of ethnic conflict and contestation of the state. With a case study of the Kurdish issue in Turkey, it examines the position of interest associations in major Kurdish province Diyarbakır in relation to political struggles between different models of social integration by exploring the relative weight of economic interests and collective identity politics in influencing associational strategies. This examination draws on the theoretical literature on interest associations and their impact on social order and democracy. In particular, the analysis adopts the framework of Streeck and Schmitter to understand the logic of associational action by looking at the environments of membership and influence. The analysis, however, modifies this framework by emphasizing the duality seen within both environments, as well as the transitional context that the contestation of the state and socio-economic changes contribute to. The empirical analysis focuses on a selection of interest associations with either de jure or de facto compulsory membership (the Chamber of Commerce and Industry; the Bar and Medical Associations; and labor unions in municipal sector). It provides an in-depth analysis of strategies of each association in relation to its membership and its interlocutors, as well as a broader analysis of organized interests in relation to other ‘partial regimes,’ that is, institutionalized sites for the political representation of social groups such as political parties and social movements that represent diverse ‘interests’ and ‘passions’ reflecting the cleavages in society. The dissertation relies on archival research and four-months of fieldwork, focusing on the last decade for the examination of associational politics.
Keywords: Civil society -- Turkey -- Diyarbakır.; Non-governmental organizations -- Turkey -- Diyarbakır.